Analisis Kinerja Keuangan Dengan Menggunakan Rasio Keuangan Pada PT. Garuda Maintenance Facility Aero Asia Tbk - Pratama, Ine Hanisa; Putri, Silviana Aulia; Nisa, Mia Kairun (EKALAYA : Jurnal Ekonomi Akuntansi, 2023)
This study aims to analyze the financial performance of PT GMF Aero Asia Tbk for the period 2020–2021 based on financial ratios. The type of research used is descriptive-quantitative, using the financial statements of PT GMF Aero Asia Tbk from 2020 to 2021. The financial ratios used as an analytical tool in this study were calculated using the calculation technique for Liquidity Ratios, Solvency Ratios, Profitability Ratios, and Activity Ratios. The results of this study indicate that the liquidity ratio has increased, but the ratio value remained below 1 time, which indicates there is a risk of an inability to meet existing short-term obligations. The solvency ratio has increased but produces a negative final value. So that the solvency ratio is considered poor, it experiences accumulated losses that exceed the total equity. Meanwhile, the profitability ratio has a negative side, which indicates that the company's operational costs are greater than revenue, so it does not earn net profit but loses. The Activity Ratio has increased from year to year, which means that companies can raise funds faster